Local buckling and ultimate strength of slender elliptical hollow sections in compression. (15th March 2016) - McCann, F.; Fang, C.; Gardner, L.; Silvestre, N.
Highlights: Numerical model of slender elliptical hollow sections in compression developed. Parametric study varied EHS aspect ratio, thickness, yield stress and imperfection amplitudes. Postbuckling behaviour of low aspect ratio EHS similar to cylindrical shells. Behaviour approached that of flat plates with increasing aspect ratio. ​New design method reflects influence of a / b ratio and slenderness on strength. Abstract: The local buckling behaviour and ultimate cross-sectional strength of tubular elliptical profiles in compression is examined in this study through numerical modelling. The numerical models were first validated against previous experimental data with good agreement observed, enabling an extensive parametric study to be performed. A total of 270 elliptical sections were simulated in order to examine the influence of cross-section aspect ratio, geometric imperfections and local slendernesses. The obtained ultimate capacities, load–deformation responses and failure modes are discussed. It was found that for lower cross-section aspect ratios the behaviour of the elliptical hollow sections (EHS) was similar to that of cylindrical shells across a number of metrics; however, as the aspect ratio increased, more plate-like stable postbuckling behaviour was observed. Imperfection sensitivity was found to decrease with increasing slenderness and aspect ratio. The influence of the shape of the initial imperfection on the strengths of the EHS columns was also assessed and was found to be generally limited. Finally, a design method has been proposed for Class 4 EHS members that reflects the reduction in capacity due to local buckling with increasing slenderness, but also recognises the improved postbuckling stability with increasing aspect ratio; the proposals were shown to provide safe and accurate predictions for the strengths of the EHS columns with nondimensional local slendernesses up to 2.5 and aspect ratios from 1.1 to 5.0.